Mapeamento de estratégias para o desenvolvimento da economia circular em propriedades suinícolas - Sales, Gabriel Fernandes (2023)
Estimates of population growth have indicated a significant increase in food consumption, causing problems related to food security and the environment. Thus, pork consumption has also intensified, and the advance of intensive pig farming brings with it some environmental impacts such as: greenhouse gas emissions, effluent generation, energy consumption, polluting waste, among others. To mitigate these effects, the Circular Economy has been approached as an innovative strategy that seeks to maximize the use of resources and minimize environmental impacts through the creation of a closed production and consumption cycle. The main objective of this dissertation was to characterize potential Circular Economy practices applied to pig farming and waste treatment, in search of a transition to a more circular business model, in order to mitigate the impacts caused in addition to providing economic benefits for pig farms. As a result, a market survey was applied with 128 pig farmers from different regions, in order to assess the level of development and knowledge of different circular strategies for waste treatment and environmental valorization. Then, a mapping of strategies was presented for the micro, meso, and macro levels based on technologies and processes that aim at sustainable development in swine production. Thus, it was possible to present a more complete vision of the potential of Circular Economy in pig farming, including its environmental implications and strategies aimed at the development of this sector.